EMBELAJARAN PENDIDIKAN AGAMA ISLAM BERMUATAN MULTIKULTURAL PADA SEKOLAH DASAR (Telaah Buku PAI Kelas 5 dan 6 Kurikulum 2013 Penerbit Erlangga) - Kurniawan Kurniawan (Jurnal Pendidikan "EDUKASIA MULTIKULTURA", 2020)
Books are learning media that serves to achieve the learning goals consumed by students. Textbooks are teaching materials that continue to develop dynamically along with the progress and demands of community development. Books are learning media that serve to achieve the learning goals consumed by students. Textbooks are teaching materials that continue to develop dynamically along with the progress and demands of community development. Textbooks are written to support a particular teaching program. While the purpose of the variable Islamic Education (PAI) can be understood by referring to the GBPP of Islamic Education in public schools, it is explained that Islamic Religious Education is a conscious effort to prepare students in believing, understanding, living and practicing Islam through guidance, teaching, and exercise by paying attention to the demands to respect others in harmony relations between religious communities in the community to realize national unity. The concept of multicultural education is based on the basic values of sympathy, tolerance, empathy, and social solidarity. The results of this multicultural education process are expected to be able to create peace and realize the efforts to overcome and prevent religious conflicts, religious radicalism, ethnic conflict, and national disintegration. Based on the discussion of Islamic Religious Education (PAI) learning and grade 5 and 6 Islamic Religious Education (PAI) book contents in Erlangga Publisher, which is associated with Multicultural values contained in each material discussion, the writer can conclude that PAI learning contains about PAI learning Al-Qur'an and Hadith, Aqidah, Morals, Fiqh, Date and Islamic Culture have been described in the PAI book. From the discussion that the author has detailed in detail in tabular form also includes the values of multicultural education. This means that in every material there is always a multicultural value, even though the weight / depth of the multicultural aspect is not the same in each material.